Analysis of Sliding Gate Mixer Machine as a Context for Engineering Learning - Mochamad Saleh (Civiliza Publishing, Indonesia., 2026)
Sliding gate systems in cement mixer machines are critical components for regulating material flow; however, their performance is often constrained by excessive friction and shear forces, particularly under maximum load conditions. Empirical observations at PT FOCON Mojokerto revealed that the sliding gate fails to operate smoothly when the hopper load reaches one ton, leading to increased actuation force demand and overheating of the pneumatic cylinder. This study aims to analyze the shear forces acting on the sliding gate based on different material contact configurations and to determine the optimal pneumatic cylinder bore diameter for efficient operation. The research employs a quantitative analytical approach grounded in classical friction theory and pneumatic force analysis, using field-observed loading conditions and validated material friction coefficients. The results demonstrate that metal-to-metal contact generates the highest shear force (925 kg), whereas the use of nylon combined with grease lubrication reduces the shear force significantly to 187.5 kg, enabling a reduction in the required pneumatic cylinder bore diameter from 155 mm to 70 mm at a working pressure of 5 bar. These findings confirm that appropriate material selection and lubrication substantially improve sliding gate performance and actuator efficiency. The study concludes that polymer-based, lubricated sliding interfaces provide a practical and economical alternative to imported components. Scientifically, this research contributes by explicitly linking tribological material properties to pneumatic actuator sizing in industrial sliding gate design.